2008
DOI: 10.1088/0957-0233/19/8/085301
|View full text |Cite
|
Sign up to set email alerts
|

Refractive index sensing of fiber optic long-period grating structures coated with a plasma deposited diamond-like carbon thin film

Abstract: Long-period grating (LPG) structures including cascaded LPGs on step index fibers and photonic crystal fibers were coated with thin films of diamond-like carbon (DLC) using plasma deposition techniques. Improvements in the coating procedures increased sensitivity to external refractive index variations indicating significant improvements in sensing capability of the hybrid structures. DLC films in the range of tens of nanometers significantly increased sensitivity of all the structures tested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(19 citation statements)
references
References 47 publications
0
19
0
Order By: Relevance
“…Deposition of uniform thin films, entirely coating the glass fibres, is one of the biggest challenges. Moreover, the cylindrical shape of fibres, which is not compatible with deposition systems designed for flat substrates, and poor adhesion of the carbon-based films to fused silica [11] make the deposition of high-quality diamond films on optical fibres difficult. May et al [12] demonstrated that it is possible to deposit highly resistive diamond on optical fibres.…”
Section: Introductionmentioning
confidence: 99%
“…Deposition of uniform thin films, entirely coating the glass fibres, is one of the biggest challenges. Moreover, the cylindrical shape of fibres, which is not compatible with deposition systems designed for flat substrates, and poor adhesion of the carbon-based films to fused silica [11] make the deposition of high-quality diamond films on optical fibres difficult. May et al [12] demonstrated that it is possible to deposit highly resistive diamond on optical fibres.…”
Section: Introductionmentioning
confidence: 99%
“…In the recent years, the combination of these two technologies somehow began to be frequent and the number of publications reporting optical fibers and diamond coating has substantially increased [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Tapering the fibre to a diameter of 25 m allowed the demonstration of an LPG with a sensitivity of 715 nm/RIU [22]. Etching the cladding of a section of standard single mode fibre containing an LPG from 125 m to approximately 100 m produced a sensitivity gain of 5 [25], while the etching an arc induced LPG to a diameter of 37 m allowed the demonstration of a sensitivity of order 20,000 nm/RIU [26]. Approaches that require the processing of the fibre, such as polishing, etching and tapering, produce significant enhancements in sensitivity, but at the cost of requiring careful packaging to compensate for the inevitable reduction in the mechanical integrity of the device.…”
Section: Introductionmentioning
confidence: 99%
“…The deposition of thin film overlays, of thickness on the order of 200 nm, of materials of refractive index higher than that of the cladding has also been investigated for the enhancement of refractive index sensitivity [25,26]. It has been shown previously experimentally and theoretically [27,28] that the effective indices of the cladding modes, and thus the central wavelengths of the core-cladding mode coupling bands of LPGs, show a high sensitivity to the optical thickness of high refractive index coatings when the coating's optical thickness is such that one of the low order cladding modes is phase matched to a mode of the waveguide formed by the coating.…”
Section: Introductionmentioning
confidence: 99%